Application of the Internet of Things in the textile industry. Issue 3 (3rd July 2019) - Manglani, Hitesh; Hodge, George L.; Oxenham, William
Abstract: The 'Internet of Things' (IoT) is at times mythologized and its purpose mistaken, and often people can become confused about what it means, does or aims to achieve; moreover, without a financial appraisal of the differences IoT can make to their own enterprise, business leaders may be content to watch and wait rather than to take a lead. This issue of Textile Progress aims to provide a guide to help navigation beyond general statements about IoT and to help those involved with the textile industry to make an informed decision about its potential value to them. The definitions of the Internet of Things (IoT) available in the literature, and those put forth by organizations working on IoT standards development, are reviewed along with its architecture, elements, standards and protocols to help provide an understanding of the concepts and goals of IoT. A broad overview of impediments challenging the progress of IoT, especially in relation to cybersecurity, is provided. This review also compares ongoing work in the application of IoT in the textile industry to that in other manufacturing sectors whilst focussing on the interpretation of IoT technologies and their potential application to the textile industry according to both technological and business perspectives. A specific case study for the spinning industry is conducted to help with evaluation of its IoT solutions and to help to address how other parts of the textile industry might benefit from its application. The case study includes evaluation of IoT solutions in the spinning industry spanning the period between ITMA 2011 to 2019, and takes information from interviews with industry executives to inform future directions of IoT in the spinning industry.